ANALISIS PENERAPAN BUSINESS MODEL CANVAS (BMC) PADA NASI BOX KYBOKS - Hakim, Ulil Akbar; Jaharuddin, Jaharuddin (Taksasila Edukasi Insani, 2023)
This study examines how the Business Model Canvas (BMC) is applied in the Kyboks rice box business. Kyboks is a unique and affordable business that faces challenges due to its remote locations. The researchers utilized BMC as a tool to map Kyboks’ business model and expand its market coverage. The research method involved descriptive research with a qualitative approach, and data was collected through interviews with a Kyboks business owner. The analysis of the collected data using a qualitative approach and BMC revealed that Kyboks incorporates all nine elements of the BMC in its operations. Kyboks targets Gen-Z, individuals in specific areas, office employees, and spicy food enthusiasts. The value propositions offered by Kyboks include good chili flavor, affordable prices, unique rice box combinations, and free delivery. Kyboks employs social media platforms, particularly Instagram, and word of mouth as distribution channels. To further expand its business reach, Kyboks should explore creative and innovative ideas, such as collaborating with influencers.Keyword: Business Model Canvas, Rice Box, Kyboks, Business Analyst